A Canadian Parlor Room-Type Approach to the Long-Term Care Insurance Puzzle - M. Martin Boyer; Philippe De Donder; Claude Fluet; Marie-Louise Leroux; Pierre-Carl Michaud (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We examine the different hypotheses which have been put forward to explain the low demand for long-term care insurance using the results from a survey of 2000 Canadians that was conducted in the autumn of 2016. Defining the natural market of long-term care insurance buyers as the one catering to individuals aged between 50 and 70, we find that a remarkable proportion of this natural market has never been approached to purchase such protection. We estimate that approximately 60% of this natural market is currently under-served. After eliminating risk perception and demand side explanations for the low market penetration of long-term care insurance, we conclude that supply-side factors and the crowding-out by government programs are the most likely culprits in explaining the low proportion of Canadians that purchase LTC insurance from private providers.
Keywords: 330